The application of a decision support system for dispensing practices when purchasing medicines - Bilbie, Joseph (Cranfield University, 2009)
In England, Dispensing Practices face the difficulty of purchasing drugs based on clinical need but must strike a balance of retaining cost effectiveness, provide value for money whilst simultaneously maximising profits. The current process of making decisions over where drugs are purchased is very much reliant on buyer intuition and supplier bias rather than extensive knowledge of costs within the supplier market. This feasibility study investigates the theoretical concept of using a decision support system as a best practise approach to identifying the most cost effective sources for Dispensing Practices buying medicines for dispensing. The research was undertaken using a deductive and inductive approach. The inductive approach was carried out in the form of questionnaires and interviews to engage practitioner perspectives. The findings suggest that a decision support system could be used by Dispensing Practices to improve their decisions over where drugs are purchased and used to enable best practise of purchasing medicine. It was proposed that despite some potential weaknesses and concerns regarding reliability it was a concept that could be adopted and utilised as an effective tool to assist healthcare professionals within their role.
Keywords: Dispensing Practice; Decision Support System; Price Comparison; Medicine; drugs; supplier market